Análise de habitações sociais na perspectiva da ergonomia do ambiente construído: estudo de caso do PROMORE - Lelis, Viviane Frascareli [UNESP] (2015)
The dwellings must ensure minimum living conditions, usability, comfort and safety to the user. The research was based on the investigation of the ergonomic conditions of social housing, by checking the anthropometric requirements. Relations were established regarding the knowledge of professionals on ergonomics associated with some environmental comfort variables and quality of housing projects PROMORE - House Economic Program in Bauru-SP-SP city. In such projects, the enthropometric requirements were verified (static and dynamic anthropometry) and environmental comfort variables compared to the degree of knowledge of ergonomics and design practice of the professionals involved. It was checked if the formation items and/or repertoire purchased by professionals, reflects positively on the quality of dwellings. The research presents exploratory property and qualitative-descriptive feature. The survey method was applied, from tools with open and closed questions. Two categories of samples were defined: the first - the professionals (architects and civil engineers PROMORE) was non probabilistic and convenience: the second, the sample of homes (those effectively developed and constructed through the PROMORE). The study was organized in three axes (exposure, construction and finding) and in six interdependent and cyclical steps, constantly being supported by the theoretical framework. The pocess of analysis and treatment of data has been basically descriptive and consisted of comparative multi-analyzes. These were arranged and organized according to the order of instruments used and they were crossed with each other, between the theoretical framework and between the conditions of knowledge or professional repertoire on ergonomics. The environmental quality checked in housing, as regards ergonomic principles, isn't necessarity associated knowledge or application of anthropometric parameters or dimensional by professionals involved in the...